2006
DOI: 10.4049/jimmunol.176.2.1266
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo-Expanded CD4+CD25+ Immunoregulatory T Cells Prevent Graft-versus-Host-Disease by Inhibiting Activation/Differentiation of Pathogenic T Cells

Abstract: CD4+CD25+ immunoregulatory T cells (Tregs) can be administered to inhibit graft-vs-host disease (GVHD) while preserving graft-vs-leukemia activity after allogeneic bone marrow transplantation in mice. Preclinical studies suggest that it is necessary to infuse as many Tregs as conventional donor T cells to achieve a clinical effect on GVHD. Thus, it would be necessary to expand Tregs ex vivo before transplantation. Two strategies have been proposed: expansion of Tregs stimulated by anti-CD3/CD28-coated microbea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 28 publications
5
98
1
Order By: Relevance
“…Previous efforts to generate T reg cells included retroviral transduction of CD4 + T cells [20], polyclonal expansion of nT reg cells [21], and induction of iT reg cells using DC [22]. We report here that conventional B2 cells efficiently convert Foxp3 -T cells into iT reg cells, at frequencies greater than seen with DC (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…Previous efforts to generate T reg cells included retroviral transduction of CD4 + T cells [20], polyclonal expansion of nT reg cells [21], and induction of iT reg cells using DC [22]. We report here that conventional B2 cells efficiently convert Foxp3 -T cells into iT reg cells, at frequencies greater than seen with DC (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…CD25 ϩ and CD25 Ϫ cells were prepared as previously described (28). Briefly, brachial, axillary, cervical, and inguinal LN and spleen were mechanically dissociated.…”
Section: Cell Preparation and Adoptive Transfermentioning
confidence: 99%
“…Therefore, polyspecific CD4 + CD25 high cells are currently being evaluated after stem cell transplantation [13]. However, under nonlymphopenic conditions as seen in patients with autoimmune diseases or in patients after organ transplantation, polyspecific Treg cells have so far been largely ineffective in controlling immune responses [5,14,15]. Instead, we and others showed that only Ag-specific Treg cells recognizing Ags from the affected tissue can control autoimmunity under nonlymphopenic conditions [14][15][16][17].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, chronic nonspecific immunosuppression causes renal dysfunction and predisposes patients to infections and increased Correspondence: Dr. Elmar Jaeckel e-mail: Jaeckel.Elmar@mh-hannover.de risk of malignancies [1]. Innate and adaptive immune responses can be controlled by Treg cells, thereby offering new therapeutic options after organ transplantation [2][3][4][5][6]. CD4 + CD25 high FOXP3 + Treg cells have been shown to be of major importance in allospecific tolerance in animal models and to influence donor-specific immune responses in transplant patients [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation